Respuesta :
1. Simplified form of: 3 a^4 * 4 b^(-2) * c^3 =
= ( 3 a^4 * 4 c^3 ) / ( b^2 )
Answer: d.
2. If a = - 5,
- a^(-2) = - ( - 5 )^(-2) = - ( 1/ 5^2 ) = - 1/25
Answer: c.
3. If m = 2 and n = - 24:
( - 2 )^(-3) * ( - 24 ) = 1 / (- 2 )^3 * ( - 24 ) = - 1 / 8 * ( - 24 ) = 24 / 8 = 3
Answer: a. 3
= ( 3 a^4 * 4 c^3 ) / ( b^2 )
Answer: d.
2. If a = - 5,
- a^(-2) = - ( - 5 )^(-2) = - ( 1/ 5^2 ) = - 1/25
Answer: c.
3. If m = 2 and n = - 24:
( - 2 )^(-3) * ( - 24 ) = 1 / (- 2 )^3 * ( - 24 ) = - 1 / 8 * ( - 24 ) = 24 / 8 = 3
Answer: a. 3
Answer:
1. The correct option is d.
2. The correct option is c.
3. The correct option is a.
Step-by-step explanation:
1.
The given expression is
[tex]3a^4b^{-2}c^3[/tex]
Using property of exponent the given expression can be written as
[tex]\frac{3a^4c^3}{b^{2}}[/tex] [tex][\because a^{-n}=\frac{1}{a^n}][/tex]
Therefore, the correct option is d.
2.
The given expression is
[tex]-a^{-2}[/tex]
Using property of exponent the given expression can be written as
[tex]-\frac{1}{a^{2}}[/tex] [tex][\because a^{-n}=\frac{1}{a^n}][/tex]
Put a=-5
[tex]-\frac{1}{(-5)^{2}}[/tex]
[tex]-\frac{1}{25}[/tex]
Therefore option c is correct.
3.
The given expression is
[tex](-m)^{-3}n[/tex]
Using property of exponent the given expression can be written as
[tex]\frac{n}{(-m)^3}[/tex]
Put m=2 and n=-24.
[tex]\frac{-24}{(-2)^3}[/tex]
[tex]\frac{-24}{-8}[/tex]
[tex]\frac{24}{8}=3[/tex]
Therefore option a is correct.